2022
DOI: 10.1039/d2nj03142f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the antibacterial activity of near-infrared light-triggered photothermal therapy using hybrid Au/ZnSe nanodumbbells

Abstract: Photothermal therapy (PTT) for bacterial infection is an effective alternative to antibiotics. However, the excitation light with short wavelength which has unsatisfactory tissue penetration and the poor photothermal (PT) effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Meanwhile, the photoacoustic intensity of the PtAg nanosheet with the NIR-II laser was significantly higher than that of the NIR-I laser (Figure 12a). The results of inhibiting tumor proliferation using PtAg nanosheets also showed that PAI-guided PTT is an [117] Copyright 2022, The Royal Society of Chemistry. f) Schematic of cysteamine and NIR-II PTT induced silver release from gold sliver hollow nanocages for therapy of multidrug-resistant bacteria infections.…”
Section: Photoacoustic Imaging-guided Photothermal Therapymentioning
confidence: 94%
See 4 more Smart Citations
“…Meanwhile, the photoacoustic intensity of the PtAg nanosheet with the NIR-II laser was significantly higher than that of the NIR-I laser (Figure 12a). The results of inhibiting tumor proliferation using PtAg nanosheets also showed that PAI-guided PTT is an [117] Copyright 2022, The Royal Society of Chemistry. f) Schematic of cysteamine and NIR-II PTT induced silver release from gold sliver hollow nanocages for therapy of multidrug-resistant bacteria infections.…”
Section: Photoacoustic Imaging-guided Photothermal Therapymentioning
confidence: 94%
“…Owing to its special structure and composition, Au/ZnSe exhibits high PT conversion efficiency and antibacterial ability ( Figure a–e). [ 117 ]…”
Section: Nir‐ii Plasmonic Nanomaterials For Theranostic Applicationsmentioning
confidence: 99%
See 3 more Smart Citations